Kennst du das Land, wo die Mangos blühn? - Donal K. Coffey (Rechtsgeschichte - Legal History, 2021)
review on: Chintan Chandrachud, The Cases that India Forgot, New Delhi: Juggernaut 2019, XIII + 229 S., ISBN 978-9353450823